Photo-cured nitride ceramic powder as well as preparation method and application thereof

The solid content, viscosity and light of the photocured nitride ceramic slurry are solved by surface modification of ternary eutectic oxide formed by lithium oxide, magnesium oxide, yttrium oxide and organophosphate dispersant on nitride ceramic powder. The problem of difficult to take into account the hardness of curing depth has achieved high-precision and high-performance production of complex structural parts, suitable for aviation, aerospace and industrial fields.

CN119306500APending Publication Date: 2025-01-14JIMEI UNIV +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411451527.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing photocured nitride ceramic slurry is difficult to take into account both the solid content, viscosity, photocuring depth and densified sintering performance, which leads to increased difficulty in preparing complex structural parts and unstable performance.

Method used

The nitride ceramic powder, surface modifier LMY (ternary eutectic oxide formed by lithium oxide, magnesium oxide, yttrium oxide) and dispersant DC (organophosphate) were mixed in a specific proportion, and prepared by stirring and ball milling. A powder with excellent dispersion is produced to form a high solids content, low viscosity, and deep light curing nitride ceramic powder.

Benefits of technology

It significantly improves the solid content, viscosity and photocuring depth of nitride ceramic slurry, reduces the sintering temperature, and improves the preparation processability and performance of complex structural parts. It is suitable for aviation, aerospace and industrial fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of light-cured nitride ceramic materials, in particular to light-cured nitride ceramic powder as well as a preparation method and application thereof. The light-cured nitride ceramic powder comprises the following components: nitride ceramic powder, a surface modifier LMY and a dispersing agent DC, the mass ratio of the nitride ceramic powder to the surface modifier LMY to the dispersing agent DC is (85-95): (5.0-10): (2.0-5.0); the surface modifier LMY is Li-Mg-Y ternary eutectic oxide formed by mixing lithium oxide, magnesium oxide and yttrium oxide according to the eutectic proportion, and the dispersing agent DC is organophosphate. Nitride ceramic slurry is prepared from the photo-cured nitride ceramic powder, the solid content of the slurry is larger than or equal to 65 wt%, the viscosity is smaller than or equal to 2500 mPas, the photo-curing depth is larger than or equal to 60 microns, and the sintering temperature of the slurry is reduced, so that the technical problem that the solid content, the viscosity, the photo-curing depth and densified sintering of the nitride ceramic slurry are difficult to consider is solved; and the manufacturability of nitride ceramic slurry photocuring 3D printing is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of photocured nitride ceramic materials, and in particular to a photocured nitride ceramic powder and a preparation method and application thereof. Background Art

[0002] Nitride ceramics, such as AlN, BN, Si3N4 and other ceramic materials, have relatively low density, high toughness, high hardness, wear resistance, corrosion resistance, excellent electromagnetic properties, excellent thermal conductivity, strong resistance to thermal shock (heated to above 1000℃ in air, rapid cooling and rapid heating will not break), high strength below 1300℃, high chemical stability and non-toxicity, etc., and have been continuously valued by researchers at home and abroad, and are widely used in metallurgy, energy, machinery, aerospace, electronics, bioengineering and other fields, especially in aviation, aerospace, electronics and bioengineering. However, due to the inherent high melting point, high strength and high hardness of nitride ceramics, the difficulty of precise preparation of complex shaped special-shaped structural parts is greatly increased.

[0003] Compared with traditional processes, photocuring 3D printing technology does not require molds, has high material utilization, high structural accuracy and stable performance, and is very suitable for the preparation of complex structural devices. The quality and service performance of photocuring 3D printed ceramic components depend on the rheological properties of the ceramic slurry, the photocuring characteristics, the printing process, and the degreasing and roasting post-treatment process. The photocuring 3D printing molding technology of oxide ceramics such as Al2O3, SiO2, and ZrO2 is relatively mature and has been applied; but the photocuring 3D printing technology for non-oxide ceramics such as Si3N4 and SiC is still in research and development, and there are still some technical difficulties to overcome, especially the technical difficulties in the process control of nitride ceramic slurry have not been overcome: At an ultraviolet wavelength of 405nm, the refractive index of Si3N4 powder (2.0978) is greater than that of common oxide powders (such as SiO2-1.5571) and Al2O3-1.7555). The refractive index difference between Si3N4 ceramic powder and the slurry photosensitive resin medium is also large, resulting in a small curing depth of the ceramic slurry, which is difficult to meet the requirements of photocuring forming.

[0004] A method for surface oxidation treatment of Si3N4 ceramic powder has been proposed. A thin SiO2 shell is formed on the surface of Si3N4 powder particles by oxidation to increase the curing depth, and then a photocuring 3D printing method is used to manufacture Si3N4 parts with complex shapes. SiO2 has a low refractive index, which can reduce the refractive index difference between the surface of Si3N4 powder and photosensitive resin, and can reduce the ultraviolet light absorption rate of Si3N4 powder, and increase the penetration depth of incident light in Si3N4 ceramic slurry. However, the solid content of Si3N4 ceramic slurry is not high, which has an adverse effect on the strength of the formed green body and the density and mechanical properties of the ceramic after sintering. In addition, the formed SiO2 thin shell will reduce the sintering temperature, and also significantly reduce the mechanical properties, high temperature properties and electromagnetic properties of Si3N4 ceramic parts. Stability.

[0005] Some researchers have also proposed using Al2O3-Y2O3 to coat Si3N4 based on the fact that Al2O3 and Y2O3 are commonly used sintering aids for Si3N4 ceramics and their refractive indices are smaller than that of Si3N4. On the one hand, this can reduce the absorption of ultraviolet light by Si3N4 powder and reduce the refractive index difference between Si3N4 powder and photosensitive resin, thereby improving the photocuring performance of Si3N4 powder; on the other hand, as a sintering aid, it can optimize the sintering densification process of Si3N4, thereby improving the mechanical properties of Si3N4 ceramics; however, this scheme has the problems of high sintering temperature (≥1700℃) and large dielectric constant and tangent loss of the sintered ceramics.

[0006] In summary, the existing photocured nitride ceramic slurry has technical difficulties in balancing the performance of solid content, viscosity, photocuring depth, and densification sintering. Summary of the invention

[0007] In order to solve the deficiencies of the prior art mentioned in the above background technology, the present application provides a photocurable nitride ceramic powder, and its technical solution is as follows: The photocured nitride ceramic powder provided in the present application comprises components including nitride ceramic powder, surface modifier LMY and dispersant DC; wherein the mass ratio of the nitride ceramic powder, the surface modifier LMY and the dispersant DC is (85-95): (5.0-10): (2.0-5.0).

[0008] In some embodiments, the nitride ceramic powder, the surface modifier LMY, and the dispersant DC are mixed in a mass ratio of (85-95): (5.0-10): (2.0-5.0).

[0009] In some embodiments, the surface modifier LMY is prepared by mixing lithium oxide (Li2O), magnesium oxide (MgO), and yttrium oxide (Y2O3) in a ratio to form a ternary eutectic oxide (Li-Mg-Y ternary eutectic oxide).

[0010] In some embodiments, the preparation process of the surface modifier LMY is: Lithium oxide powder, magnesium oxide powder and yttrium oxide powder are weighed according to the eutectic ratio, added into an ethanol solvent, and stirred and dispersed to obtain a mixture M; the mixture M is ball-milled to obtain a uniformly dispersed slurry; the ethanol solvent in the slurry is volatilized to obtain the powdered surface modifier LMY.

[0011] In some embodiments, the ball milling treatment conditions are ball milling at a rate of 180-300 r / min for 6-10 hours; volatilizing the ethanol solvent in the slurry under normal temperature and atmospheric environment, or evaporating and removing the ethanol solvent in an oven below 50-60°C to obtain the powdered surface modifier LMY.

[0012] In some embodiments, the dispersant DC is an organophosphate.

[0013] In some embodiments, the particle size of the nitride ceramic powder is 3-5 μm.

[0014] The present application also provides a method for preparing the light-cured nitride ceramic powder as described above, which comprises the following steps: The surface modifier LMY is prepared by mixing lithium oxide, magnesium oxide and yttrium oxide in a ratio to form a ternary eutectic oxide; Weigh the nitride ceramic powder, the surface modifier LMY powder, and the dispersant DC according to the weight ratio of the formula; first add the nitride ceramic powder into the ethanol solvent while stirring and dispersing, then add the surface modifier LMY powder and stir and disperse, and finally add the dispersant DC and stir and disperse evenly to obtain a pre-dispersed nitride ceramic powder slurry; The pre-dispersed nitride ceramic powder slurry is heated and reacted while being stirred until the ethanol solvent is evaporated to dryness, thereby obtaining a ceramic powder; The ceramic powder is air-dried and the dried powder is sieved to obtain the nitride ceramic powder.

[0015] In some embodiments, in the step of preparing the surface modifier LMY, lithium oxide powder, magnesium oxide powder and yttrium oxide powder are weighed according to the eutectic ratio, added to an ethanol solvent, and stirred and dispersed to obtain a mixture M; the mixture M is ball-milled to obtain a uniformly dispersed slurry; the ethanol solvent in the slurry is volatilized to obtain the powdered surface modifier LMY; Weigh the nitride ceramic powder, the surface modifier LMY powder, and the dispersant DC according to the weight ratio of the formula; first add the nitride ceramic powder into the ethanol solvent while stirring and dispersing, then add the surface modifier LMY powder and stir and disperse, and finally add the dispersant DC and stir and disperse for (2-4) hours to obtain a pre-dispersed nitride ceramic powder slurry; The pre-dispersed nitride ceramic powder slurry is heated while being stirred until the ethanol solvent is evaporated to dryness, thereby obtaining a ceramic powder; wherein the heating temperature is 50-60° C., and the stirring rate is (300-600) r / min; The dried powder is sieved through a 200-mesh sieve to obtain the nitride ceramic powder.

[0016] The present application also provides the use of the above-mentioned photocurable nitride ceramic powder in the preparation of nitride ceramic slurry for photocurable 3D printing.

[0017] Based on the above, compared with the prior art, this application has the following beneficial effects: The photocured nitride ceramic powder provided in this application is used to prepare a nitride ceramic slurry, the solid content of the slurry is ≥65wt%, the viscosity is ≤2500mPa∙s, the photocuring depth is ≥60μm, and the slurry sintering temperature is reduced, thereby solving the technical problem that the solid content, viscosity, photocuring depth, and densification sintering of the nitride ceramic slurry are difficult to take into account, and significantly improving the processability of nitride ceramic slurry photocuring 3D printing. The high-precision, high-performance complex structure nitride ceramic products prepared by the nitride ceramic slurry can be better applied to aviation, aerospace, medical and industrial fields.

[0018] Other features and beneficial effects of the present application will be described in the following description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other beneficial effects of the present application can be achieved and obtained by the structures specifically pointed out in the description and claims. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments; the technical features designed in different implementation modes of the present application described below can be combined with each other as long as they do not conflict with each other; based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0020] In the description of this application, it should be noted that all terms (including technical terms and scientific terms) used in this application have the same meanings as those generally understood by ordinary technicians in the field to which this application belongs, and cannot be understood as limitations on this application; it should be further understood that the terms used in this application should be understood to have meanings consistent with the meanings of these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this application.

[0021] The present application provides an operation example of a method for preparing a photocured nitride ceramic powder, and the specific steps are as follows: Step 1: Lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder are weighed according to the eutectic ratio (i.e., the ratio of the ternary eutectic oxide), added together into an ethanol solvent for stirring and dispersion; then transferred into a planetary ball mill for ball milling at a rate of 180-300 r / min for 6-10 hours to obtain a uniformly dispersed slurry; thereafter, the ethanol solvent is volatilized in an atmospheric environment or evaporated and removed in an oven below 50-60°C to obtain a surface modifier LMY powder for standby use.

[0022] Step 2: Weigh the nitride ceramic powder, surface modifier LMY powder and dispersant DC according to the mass ratio of (85-95): (5.0-10): (2.0-5.0); first, add the nitride ceramic powder into the ethanol solvent under low-speed stirring while stirring to disperse it, then add the surface modifier LMY powder and stir and disperse it at high speed, and finally add the dispersant DC and stir for (2-4) hours to obtain a pre-dispersed nitride ceramic powder slurry.

[0023] The dispersant DC is an organic phosphate; and the particle size of the nitride ceramic powder is 0.5 to 5 μm.

[0024] Step 3: The pre-dispersed nitride ceramic powder slurry is poured into a reactor equipped with a high-speed stirrer and a heating device, and reacted at a heating temperature of 50-60°C and a stirring rate of (300-600) r / min until the ethanol solvent is completely evaporated to obtain a ceramic powder.

[0025] Step 4: The ceramic powder is spread out in a cool indoor environment for further drying until the solvent is completely removed, and finally passed through a 200-mesh sieve to obtain a nitride ceramic powder material with excellent dispersibility in a photosensitive acrylic resin system and a small refractive index for ultraviolet light of 355 to 405 nm.

[0026] The present invention provides the following examples and comparative examples to verify the effects of the present application: Example 1 The preparation process of this embodiment is as follows: Step 1: Lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder were weighed according to the eutectic ratio (i.e., the ratio of the ternary eutectic oxide), and added together into an ethanol solvent for stirring and dispersion; then transferred into a planetary ball mill for ball milling at a rate of 180 r / min for 10 hours to obtain a uniformly dispersed slurry; thereafter, the ethanol solvent was evaporated and removed in an oven below 50° C. to obtain a surface modifier LMY powder for standby use.

[0027] Among them, lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder were weighed according to the eutectic molar ratio of 2:5:3.

[0028] Step 2: Weigh nitride ceramic powder, surface modifier LMY powder, and dispersant DC; first, add the nitride ceramic powder into the ethanol solvent under low-speed stirring while stirring to disperse it, then add the surface modifier LMY powder and stir and disperse it at high speed, and finally add the dispersant DC and stir for 2 hours to obtain a pre-dispersed nitride ceramic powder slurry.

[0029] Among them, the nitride ceramic powder uses silicon nitride ceramic powder with a particle size of 1 to 3 μm, with an amount of 1000g; the surface modifier LMY (a mixture of ternary eutectic oxides of lithium oxide (Li2O), magnesium oxide (MgO), and yttrium oxide (Y2O3)) is used in an amount of 60g; the dispersant DC is an organic phosphate ester, with an amount of 30g.

[0030] Step 3: The pre-dispersed nitride ceramic powder slurry was poured into a reactor equipped with a high-speed stirrer and a heating device, and reacted at a heating temperature of 50° C. and a stirring rate of 500 r / min until the ethanol solvent was completely evaporated to obtain a ceramic powder.

[0031] Step 4: The ceramic powder is spread out in a cool indoor environment for further drying until the solvent is completely removed, and finally passed through a 200-mesh sieve to obtain a nitride ceramic powder material with excellent dispersibility in a photosensitive acrylic resin system and a small refractive index for ultraviolet light of 355 to 405 nm.

[0032] In this embodiment, the amount of ethanol solvent used is sufficient to fully immerse the raw materials (nitride ceramic powder, surface modifier LMY, dispersant DC), and the nitride ceramic powder, surface modifier LMY, and dispersant DC can be fully stirred and mixed in the solvent.

[0033] Example 2 The preparation process of this embodiment is as follows: Step 1: Lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder were weighed according to the eutectic ratio (i.e., the ratio of the ternary eutectic oxide), and added together into an ethanol solvent for stirring and dispersion; then transferred into a planetary ball mill for ball milling at a rate of 300 r / min for 6 hours to obtain a uniformly dispersed slurry; thereafter, the ethanol solvent was evaporated and removed in an oven below 60°C to obtain a surface modifier LMY powder for standby use.

[0034] Among them, lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder were weighed according to the eutectic molar ratio of 2:5:3.

[0035] Step 2: Weigh nitride ceramic powder, surface modifier LMY powder, and dispersant DC; first, add the nitride ceramic powder into the ethanol solvent under low-speed stirring while stirring to disperse it, then add the surface modifier LMY powder and stir and disperse it at high speed, and finally add the dispersant DC and stir for 2 hours to obtain a pre-dispersed nitride ceramic powder slurry.

[0036] Among them, the nitride ceramic powder uses silicon nitride ceramic powder with a particle size of 1 to 3 μm, with an amount of 1000g; the surface modifier LMY (a mixture of ternary eutectic oxides of lithium oxide (Li2O), magnesium oxide (MgO), and yttrium oxide (Y2O3)) is used in an amount of 100g; and the dispersant DC is an organic phosphate ester, with an amount of 50g.

[0037] Step 3: The pre-dispersed nitride ceramic powder slurry was poured into a reactor equipped with a high-speed stirrer and a heating device, and reacted at a heating temperature of 60° C. and a stirring rate of 500 r / min until the ethanol solvent was completely evaporated to obtain a ceramic powder.

[0038] Step 4: The ceramic powder is spread out in a cool indoor environment for further drying until the solvent is completely removed, and finally passed through a 200-mesh sieve to obtain a nitride ceramic powder material with excellent dispersibility in a photosensitive acrylic resin system and a small refractive index for ultraviolet light of 355 to 405 nm.

[0039] In this embodiment, the amount of ethanol solvent used is sufficient to fully immerse the raw materials (nitride ceramic powder, surface modifier LMY, dispersant DC), and the nitride ceramic powder, surface modifier LMY, and dispersant DC can be fully stirred and mixed in the solvent.

[0040] Example 3 The preparation process of this embodiment is as follows: Step 1: Lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder were weighed according to the eutectic ratio (i.e., the ratio of the ternary eutectic oxide), and added together into an ethanol solvent for stirring and dispersion; then transferred into a planetary ball mill for ball milling at a rate of 240 r / min for 8 hours to obtain a uniformly dispersed slurry; thereafter, the ethanol solvent was evaporated and removed in an oven below 55°C to obtain a surface modifier LMY powder for standby use.

[0041] Among them, lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder were weighed according to the eutectic molar ratio of 2:5:3.

[0042] Step 2: Weigh nitride ceramic powder, surface modifier LMY powder, and dispersant DC; first, add the nitride ceramic powder into the ethanol solvent under low-speed stirring while stirring to disperse it, then add the surface modifier LMY powder and stir and disperse it at high speed, and finally add the dispersant DC and stir for 2 hours to obtain a pre-dispersed nitride ceramic powder slurry.

[0043] Among them, the nitride ceramic powder uses aluminum nitride ceramic powder with a particle size of 3 to 5 μm, with an amount of 1000g; the surface modifier LMY (a mixture of ternary eutectic oxide components of lithium oxide (Li2O), magnesium oxide (MgO), and yttrium oxide (Y2O3)) is used in an amount of 60g; the dispersant DC is an organic phosphate ester, with an amount of 50g.

[0044] Step 3: The pre-dispersed nitride ceramic powder slurry was poured into a reactor equipped with a high-speed stirrer and a heating device, and reacted at a heating temperature of 55° C. and a stirring rate of 500 r / min until the ethanol solvent was completely evaporated to obtain a ceramic powder.

[0045] Step 4: The ceramic powder is spread out in a cool indoor environment for further drying until the solvent is completely removed, and finally passed through a 200-mesh sieve to obtain a nitride ceramic powder material with excellent dispersibility in a photosensitive acrylic resin system and a small refractive index for ultraviolet light of 355 to 405 nm.

[0046] In this embodiment, the amount of ethanol solvent used is sufficient to fully immerse the raw materials (nitride ceramic powder, surface modifier LMY, dispersant DC), and the nitride ceramic powder, surface modifier LMY, and dispersant DC can be fully stirred and mixed in the solvent.

[0047] Comparative Example 1 The difference between this comparative example and Example 1 is that: The raw materials of the surface modifier are aluminum oxide and yttrium oxide, that is, the comparative example uses aluminum oxide and yttrium oxide to replace lithium oxide, magnesium oxide and yttrium oxide in step 1 of Example 1, and the surface modifier is prepared by mixing the aluminum oxide and yttrium oxide composition according to a eutectic ratio (the molar ratio of the aluminum oxide and yttrium oxide eutectic is 5:5).

[0048] The dispersant DC in step 2 is polyacrylate KOS110, and the ratio of nitride ceramic powder, surface modifier and dispersant DC is 8.2kg:0.8kg:1.0kg.

[0049] The other steps and preparation conditions are consistent with those in Example 1.

[0050] Comparative Example 2 The difference between this comparative example and Example 1 is only that: The raw materials of the surface modifier are aluminum oxide and yttrium oxide (i.e., the comparative example uses aluminum oxide and yttrium oxide to replace lithium oxide, magnesium oxide, and yttrium oxide in step 1 of Example 1), and the surface modifier is prepared by mixing aluminum oxide and yttrium oxide compositions according to a eutectic ratio (the molar ratio of aluminum oxide to yttrium oxide eutectic is 5:5). The other steps and preparation conditions are the same as those of Example 1.

[0051] Comparative Example 3 The difference between this comparative example and Example 1 is that the dispersant DC in step 2 is polyacrylate KOS110, and the other steps and preparation conditions are consistent with those in Example 1.

[0052] Comparative Example 4 The difference between this comparative example and Example 1 is that the ratio of nitride ceramic powder, surface modifier and dispersant DC in step 2 is 8.2 kg: 0.8 kg: 1.0 kg. The other steps and preparation conditions are the same as those in Example 1.

[0053] The photocurable nitride ceramic powders prepared in the examples and comparative examples were used to prepare photocurable nitride ceramic slurries in a photosensitive acrylic resin system, and the corresponding properties were tested, as shown in Table 1: The process of preparing the photocurable nitride ceramic powder into the photocurable nitride ceramic slurry is as follows: The photocurable nitride ceramic slurry is composed of photocurable nitride ceramic powder, polyacrylate, dispersant DC, stabilizer and photoinitiator. The raw material components are weighed according to the formula ratio, and the stabilizer, dispersant DC and photoinitiator are added to the polyacrylate in sequence while stirring and stirred for 2 hours to mix evenly to obtain a uniformly dispersed photosensitive resin system. The prepared photocurable nitride ceramic powder is added to the photosensitive resin system while stirring and mixed, and stirred at a speed of 200r / min for 2 hours, and then the material is transferred to a planetary ball mill and ball-milled at a speed of 200r / min for 24 hours to obtain a photocurable nitride ceramic slurry.

[0054] Wherein, the specific formula of each embodiment and comparative example is: Example 1 and Comparative Examples 1-4: The amount of photocured nitride ceramic powder is 1090g, the amount of polyacrylate is 311g, which is prepared by mixing 1,6-hexanediol diacrylate and ditrimethylolpropane triacrylate in a mass ratio of 1:1; the dispersant DC is organic phosphate, the amount of which is 46g, the stabilizer is KH570, the amount of which is 109g, and the photoinitiator is TPO, the amount of which is 16g.

[0055] Example 2: The amount of photocurable nitride ceramic powder is 1150g, the amount of polyacrylate is 493g, which is prepared by mixing polysiloxane acrylate and ditrimethylolpropane tetraacrylate in a mass ratio of 1:1; the dispersant DC is organic phosphate, the amount of which is 66g; the stabilizer is KH570, the amount of which is 131g; the photoinitiator is TPO, the amount of which is 25g.

[0056] Example 3: The amount of photocurable nitride ceramic powder is 1110g, the amount of polyacrylate is 476g, which is prepared by mixing 1,6-hexanediol diacrylate and polysiloxane acrylate in a mass ratio of 1:1; the dispersant DC is organic phosphate, the amount of which is 63g; the stabilizer is KH570, the amount of which is 127g; the photoinitiator is TPO, the amount of which is 24g.

[0057] Table 1

[0058] The testing process and important parameters of the photocuring depth are as follows: add the prepared nitride ceramic slurry into the storage bin of the SLA-3D printing equipment, and set the printing parameters according to the laser power factor of 0.56-0.72, the scanning rate of 2000-3500mm / s, the single layer thickness of the material 50-60μm, and the cross-sectional size of the test piece model of 10mm×10mm. Start the printing system, lay 3-4 layers of material, and perform single-layer scanning and curing on the test piece at the rated laser output power; take out the cured single-layer test piece, clean off the slurry adhering to the surface of the test piece, and use a micrometer to measure the thickness of the test piece to obtain the photocuring depth of the slurry.

[0059] The test process and important parameters of sedimentation rate are as follows: in the atmosphere, room temperature, and light-proof environment, the prepared nitride ceramic slurry is placed in a clean, scaled transparent measuring cup, and left to stand for different time periods of 0h, 100h, 200h, and 300h, and 5.0-10.0g of slurry samples are taken at the same height from the liquid surface. The samples are placed in a clean and dry porcelain boat, and degreased in a N2 atmosphere at room temperature to 1000-1050℃, and the thermal weight loss rate is measured, and compared with the 0h slurry sample to convert the sample sedimentation rate.

[0060] From Table 1 we can see that: 1. The embodiment of the present application solves the technical problem of the solid content, viscosity, photocuring depth and densification sintering of the photocured nitride ceramic slurry by composite modification of the surface of the nitride ceramic powder. Among them, the ternary eutectic oxide (surface modifier LMY) of the present application is used as a surface modifier to coat the nitride ceramic powder particles, reduce the refractive index of the nitride powder under ultraviolet light, and improve the photocurability of the slurry; at the same time, it is the best sintering aid for nitride ceramics such as silicon nitride and aluminum nitride, which can reduce the firing temperature to 1550-1650°C, reduce the difficulty of densification sintering, and significantly improve the density of the sintered product. The fired ceramic has high thermal conductivity and strength, and the dielectric constant and tangent loss are controllable.

[0061] The photocured nitride ceramic powder prepared in Example 1 of the present application is used to prepare a nitride ceramic slurry, the solid content of the slurry is ≥65wt%, the viscosity is ≤2500mPa∙s, the photocuring depth is ≥60μm, and the slurry sintering temperature is reduced, thereby solving the technical problem that the solid content, viscosity, photocuring depth, and densification sintering of the nitride ceramic slurry are difficult to take into account, and significantly improving the processability of the photocuring 3D printing of the nitride ceramic slurry. The high-precision, high-performance complex structure nitride ceramic products prepared by the nitride ceramic slurry can be better applied to aviation, aerospace, medical and industrial fields.

[0062] 2. From the comparison results of the comparative examples and the embodiments, it can be seen that: If the aluminum oxide and yttrium oxide composition is conventionally used to replace the surface modifier LMY specified in the present application, during the preparation process, the aluminum oxide and yttrium oxide composition is not as good as the surface modifier LMY in terms of the curing depth of the slurry, and the obtained light-cured nitride ceramic powder has poor effect; If polyacrylate KOS110, polymer block copolymer dispersant KOS190 and other dispersants are used, the effect of such dispersants on slurry viscosity and curing depth is not as good as that of organic phosphate dispersant DC during the preparation process, and the obtained light-cured nitride ceramic powder has poor effect; If the preparation ratio of the nitride ceramic powder, the surface modifier LMY, and the dispersant DC exceeds the specified range of the present application, the solid content, the viscosity of the slurry, and the curing depth of the slurry prepared by the photocured nitride ceramic powder will be damaged to varying degrees.

[0063] It should be noted that: In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values.

[0064] The specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments of the present application, but are not intended to limit the present application. Those skilled in the art may make adaptive adjustments within the scope of the present application.

[0065] In addition, unless otherwise specified, the raw materials used may also be conventional commercial products in the art, or prepared by conventional methods in the art; that is, the reagents and instruments used in this embodiment are not indicated with information such as the manufacturer, and are all conventional products that can be purchased on the market.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A photocured nitride ceramic powder, characterized in that: Its components include nitride ceramic powder, surface modifier LMY and dispersant DC; Wherein, the mass ratio of the nitride ceramic powder, the surface modifier LMY, and the dispersant DC is (85-95): (5.0-10): (2.0-5.0).

2. The photocured nitride ceramic powder according to claim 1, characterized in that: The nitride ceramic powder, the surface modifier LMY and the dispersant DC are mixed in a mass ratio of (85-95): (5.0-10): (2.0-5.0) to obtain the nitride ceramic powder.

3. The photocured nitride ceramic powder according to claim 1, characterized in that: The surface modifier LMY is prepared by mixing lithium oxide, magnesium oxide and yttrium oxide in a ratio to form a ternary eutectic oxide.

4. The photocured nitride ceramic powder according to claim 1, characterized in that: The preparation process of the surface modifier LMY is as follows: Weighing lithium oxide powder, magnesium oxide powder and yttrium oxide powder according to the eutectic ratio, added to an ethanol solvent, and stirred to obtain a mixture M; The mixture M is ball-milled to obtain a uniformly dispersed slurry; The ethanol solvent in the slurry is volatilized to obtain the surface modifier LMY in powder form.

5. The photocured nitride ceramic powder according to claim 4, characterized in that: The ball milling treatment conditions are ball milling at a rate of 180 to 300 r / min for 6 to 10 hours; The ethanol solvent in the slurry is volatilized under normal temperature and atmospheric environment, or the ethanol solvent is evaporated and removed in an oven at 50 to 60° C. to obtain the surface modifier LMY in powder form.

6. The photocured nitride ceramic powder according to claim 1, characterized in that: The dispersant DC is an organic phosphate.

7. The photocured nitride ceramic powder according to claim 1, characterized in that: The particle size of the nitride ceramic powder is 3-5 μm.

8. A method for preparing the photocured nitride ceramic powder according to any one of claims 1 to 7, characterized in that: The following steps are involved: The surface modifier LMY is prepared by mixing lithium oxide, magnesium oxide and yttrium oxide in a ratio to form a ternary eutectic oxide; According to the weight ratio of the formula, the nitride ceramic powder, the surface modifier LMY powder and the dispersant DC are weighed; the nitride ceramic powder is first added to the ethanol solvent while being stirred and dispersed, then the surface modifier LMY powder is added and stirred and dispersed, and finally the dispersant DC is added and stirred and dispersed evenly to obtain a pre-dispersed nitride ceramic powder slurry; The pre-dispersed nitride ceramic powder slurry is heated and reacted while being stirred until the ethanol solvent is evaporated to dryness, thereby obtaining a ceramic powder; The ceramic powder is air-dried and the dried powder is sieved to obtain the nitride ceramic powder.

9. The method for preparing the photocured nitride ceramic powder according to claim 8, characterized in that: In the step of preparing the surface modifier LMY, lithium oxide powder, magnesium oxide powder and yttrium oxide powder are weighed according to the eutectic ratio, added into an ethanol solvent, and stirred and dispersed to obtain a mixture M; the mixture M is ball-milled to obtain a uniformly dispersed slurry; the ethanol solvent in the slurry is volatilized to obtain the powdered surface modifier LMY; Weigh the nitride ceramic powder, the surface modifier LMY powder, and the dispersant DC according to the weight ratio of the formula; first add the nitride ceramic powder into the ethanol solvent while stirring and dispersing, then add the surface modifier LMY powder and stir and disperse, and finally add the dispersant DC and stir and disperse for (2-4) hours to obtain a pre-dispersed nitride ceramic powder slurry; The pre-dispersed nitride ceramic powder slurry is heated while being stirred until the ethanol solvent is evaporated to dryness, thereby obtaining a ceramic powder; wherein the heating temperature is 50-60° C., and the stirring rate is (300-600) r / min; The dried powder is sieved through a 200-mesh sieve to obtain the nitride ceramic powder.

10. Use of the photocurable nitride ceramic powder according to any one of claims 1 to 7 in preparing nitride ceramic slurry for photocurable 3D printing.

Citation Information

Patent Citations

  • Method for low-temperature sintering of β-silicon nitride ceramics under normal pressure

    CN102276260A

  • Index matched composite materials and light sources incorporating the same

    CN104755966A

  • Refractive index-matched additives for photo-curable compositions

    CN109791373A

  • Slurry for photocuring 3D printing and preparation method thereof, and silicon nitride ceramic

    CN110357642A

  • Light-transmitting ceramic sintered body and method for producing same

    CN110418773A